2021
DOI: 10.1080/09585192.2021.1964571
|View full text |Cite
|
Sign up to set email alerts
|

Responsible leadership during international assignments: a novel approach toward expatriation success

Abstract: Adopting a responsible leadership (RL) lens and drawing on intergroup behavior and social identity theory, we analyze a sample of 111 expatriates using partial least squares structural equation modeling (PLS-SEM). Our findings indicate that RL enacted by host-country supervisors is positively associated with international assignees' cross-cultural adjustment and affective wellbeing at work, in turn leading to better expatriate performance. RL may thus facilitate adjustment and well-being in the host country. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 134 publications
(163 reference statements)
0
7
0
Order By: Relevance
“…From our findings, we derive two theoretical implications based on the gaps in the literature in the following areas, one, the confluence of factors that impact SWB has been understudied in the SIE literature, and two, specifically, the role of societal influences on the SWB of the SIEs. Our findings have implications for theory on SWB of the SIEs (Froese & Peltokorpi, 2013;Mäkelä et al, 2017;Waibel et al, 2018;Presbitero, 2020;Marques et al, 2021). It has been observed that an unhappy and dissatisfied employee cannot work effectively (Gustainiene & Endriulaitiene, 2009).…”
Section: Implications For Theorymentioning
confidence: 62%
See 1 more Smart Citation
“…From our findings, we derive two theoretical implications based on the gaps in the literature in the following areas, one, the confluence of factors that impact SWB has been understudied in the SIE literature, and two, specifically, the role of societal influences on the SWB of the SIEs. Our findings have implications for theory on SWB of the SIEs (Froese & Peltokorpi, 2013;Mäkelä et al, 2017;Waibel et al, 2018;Presbitero, 2020;Marques et al, 2021). It has been observed that an unhappy and dissatisfied employee cannot work effectively (Gustainiene & Endriulaitiene, 2009).…”
Section: Implications For Theorymentioning
confidence: 62%
“…The cognitive part has to do with individuals' perception and evaluation of how their lives are in comparison to the standard norms all over the world or to their neighbors. Shaffer, Kraimer, Chen, and Bolino (2012) note that SWB is an intrinsic career outcome, whereas recent works have incorporated SWB in the context of expatriates' social and personal environment (Mäkelä, Lämsä, Heikkinen, & Tanskanen, 2017; Marques, Miska, Crespo, & Branco, 2021; Waibel, Aevermann, & Rueger, 2018). It is within this background the current study is undertaken to study SWB among expatriates.…”
Section: Introductionmentioning
confidence: 99%
“…The individual EWB of our respondents can only be addressed through responsible leadership of the organisation and policies and practices which do not trade performance for well-being (Marques et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The individual EWB of our respondents can only be addressed through responsible leadership of the organisation and policies and practices which do not trade performance for well-being (Marques et al, 2021). As Beer et al (2015) argued what is needed is a wider view of stakeholders and a more contextual and multi-layered approach to the long-term requirements of the relevant stakeholders, in which all benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a growing body of research conceptualize and operationalized reflective measures using CCA JSTP 33,3 (e.g. Marques et al, 2023;Oubrich et al, 2021). Further, we utilized Hayes ( 2017) PROCESS macro because it examines individual paths together with the mediation and moderated mediation effects.…”
Section: Methodsmentioning
confidence: 99%